“Aušros” originalų ir senosios periodikos išsaugojimo problemos - Vėlavičienė, Silvija (Knygotyra, 1995)
The National M. Mažvydas Library owns two full completes of “Aušra” (1883–1886) and some scattered editions of different years. There are eight other completes in the major Lithuanian libraries. The data about the storage of this periodical outside Lithuania is presented as well. It would be very important to gather statistics about the preserved “Aušra” because the sources that are available at present are not full and reliable. The main problem of preservation of the “Aušra” and other old Lithuanian periodicals is the acidic paper of law quality. The National Library is working on their preservation by restoring the originals and producing microforms “Aušra” is of small format and that helps to store and microfilm it. The other periodicals of the large format are not so easy to keep. The microfilming of those is extremely expensive and they present complex problems for restorators. Though the possibilities of the libraries to preserve the periodicals are very low, “Aušra” is in no immediate danger. The facsimile publication of it published in Chicago is a unique example of salvation of the old periodicals. 200 copies of this publication reached Lithuania with the first package of books for Lithuania from the US.